Formulation and evaluation of a tropical fruit compote enriched with gelatinized quinoa flour - Taramona-Ruiz, Luis A. (2024)
Compote is a widely consumed food among children and a favorable target for finding new formulations that combat food insecurity and child malnutrition. The objective of this study was to evaluate alternatives for the formulation and preparation of compotes based on tropical fruits and gelatinized quinoa flour (Chenopodium quinoa). The fruits used were guava, mango and passion fruit. A completely randomized block experimental design was developed with three treatments and 80 repetitions. The treatments used differ only in the composition of the compote, with a common production procedure that included a pasteurization operation by heat treatment that guaranteed safety. The product was sensory evaluated using a facial hedonic scale; Physicochemical and microbiological tests were carried out, as well as an analysis of the nutritional value of the most widely accepted compote. ANOVA was applied with a statistical value p:<0.05 using the STATGRAPHICS statistical software. The formulations were differentiated by the concentrations of guava and quinoa: F1 (guava 55.77 %, quinoa flour 23.91 %), F2 (guava 63.74 %; quinoa flour 15.94 %) and F3 (guava 71 .71 %; quinoa flour 7.97 %); maintaining for the three formulations, in similar proportions the rest of the constituents composed of mango, passion fruit, sugar, citric acid and vitamin C. F3 was the one with the greatest acceptability, at the same time that it met the established physicochemical, nutritional and microbiological requirements. in the standards used as a reference, so that the quality and safety of the compote is guaranteed.